PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DURAQUIPT CEMERLANG DEPOK - Amanda (Jurnal Menara, 2024)
The purpose of this research is to find out whether work stress and the work environment influence employee performance at PT. Duraquipt Cemerlang Depok. The method used is quantitative. The sampling technique used random sampling with reference to the Slovin formula with a population of 175 and a significance level of 5%, from the calculation results the sample was obtained as many as 122 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. Work stress has a positive and significant effect on performance, this can be seen from (0.000) being greater than 0.05 and the t-count (4.590) being greater than the t-table (1.98), meaning a decrease in performance for PT employees. Duraquipt Cemerlang can be affected by increased work stress in employees. The work environment has a positive and significant effect on performance, this can be seen from (0.000) being smaller than 0.05 and the t-count (5.697) being greater than the t-table (1.98), meaning an increase in performance for PT employees. Duraquipt Cemerlang is influenced by a good work environment. Work stress and the work environment simultaneously have a significant effect on the performance of PT employees Brilliant Duraquipt.